Oncogenic KRAS effector USP13 promotes metastasis in non-small cell lung cancer through deubiquitinating β-catenin - Yanguan Guo; Jiaxin Tian; Yongjian Guo; Cong Wang; Congcong Chen; Songwang Cai; Wenliang Yu; Binghe Sun; Jin Yan; Zhonghua Li; Jun Fan; Qi Qi; et al. (Cell Reports, 2023)
Summary: KRAS mutations are frequently detected in non-small cell lung cancers (NSCLCs). Although covalent KRASG12C inhibitors have been developed to treat KRASG12C-mutant cancers, effective treatments are still lacking for other KRAS-mutant NSCLCs. Thus, identifying a KRAS effector that confers poor prognosis would provide an alternative strategy for the treatment of KRAS-driven cancers. Here, we show that KRAS drives expression of deubiquitinase USP13 through Ras-responsive element-binding protein 1 (RREB1). Elevated USP13 promotes KRAS-mutant NSCLC metastasis, which is associated with poor prognosis in NSCLC patients. Mechanistically, USP13 interacts with and removes the K63-linked polyubiquitination of β-catenin at lysine 508, which enhances the binding between β-catenin and transcription factor TCF4. Importantly, we identify 2-methoxyestradiol as an effective inhibitor for USP13 from a natural compound library, and it could potently suppress the metastasis of KRAS-mutant NSCLC cells in vitro and in vivo. These findings identify USP13 as a therapeutic target for metastatic NSCLC with KRAS mutations.